How production firms adapt to war: The case of Liberia - Topher L. McDougal (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
How do production firms adapt to civil war? The answer to this question will inform the potential for economic development during and after conflict. Many businesses survive violent conflict, and in some cases even thrive. Understanding these successes will help policymakers to support the 'coping economy' during civil wars, and to understand better the post-conflict economy as a system. In this paper I use the case of production firms operating in Liberia's capital, Monrovia, during the country's civil war to argue that successful wartime firms continually adapt their supply chain structures in response to a shifting combat frontier by dispersing their functions spatially and temporally. Such adaptability depends on the rapid gathering (via business networks) and processing (at the place of production) of information. This contention represents a micro-level explanation for, and also a conditioning of, the generally accepted view that industries that survive civil war tend to be non-capital intensive and non-trade intensive.
Keywords: H56; L11; L52; Q34; 330; production firms; civil war; conflict economics; post-conflict recovery; economic resiliency; Liberia